2021
DOI: 10.1002/ajmg.a.62123
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and behavior in children and adolescents with tuberous sclerosis complex

Abstract: Sleep disorders are frequent in tuberous sclerosis complex (TSC) during the developmental age but are not well characterized. Forty‐six TSC patients and 46 healthy age‐ and sex‐matched controls were enrolled. Their parents completed the Sleep Disturbances Scale for Children (SDSC) and the Child Behavior Checklist (CBCL). A total of 17.4% of the TSC patients obtained a total pathologic score at the SDSC versus 4.4% in the control group (p = 0.024). 45.7% of individuals with TSC reported a pathologic score in at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Sleep disorders appeared to be significantly more frequent in patients reporting at least one neuropsychiatric disorder, and a statistically significant association was found also for the two subscales of DIMS and SBD. These results confirm that neuropsychiatric disorders confer a high risk for experiencing sleep disturbances, and are in good agreement with a recent paper reporting a positive correlation between SDSC and behavioral/emotional disturbances evaluated with a standardized questionnaire [12].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Sleep disorders appeared to be significantly more frequent in patients reporting at least one neuropsychiatric disorder, and a statistically significant association was found also for the two subscales of DIMS and SBD. These results confirm that neuropsychiatric disorders confer a high risk for experiencing sleep disturbances, and are in good agreement with a recent paper reporting a positive correlation between SDSC and behavioral/emotional disturbances evaluated with a standardized questionnaire [12].…”
Section: Discussionsupporting
confidence: 92%
“…A recent registry study evaluating TSC related manifestations of more than 2000 subjects, found that sleep disorders are the second most common TAND, with a 43.9% overall prevalence [11], but no detail on the type of sleep disorders nor on the association with epilepsy and/or TAND was available. A questionnaire-based study recently published found a total of 17.4% of patients with TSC presenting a positive score [12]. Finally, a recent meta-analysis study evaluated the prevalence of sleep disorders in different genetic syndromes, and it emerged that in TSC insomnia and excessive daytime sleepiness have such a prevalence that they should be considered as part of a priority assessment [1].…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between sleep—its quality, duration, any disturbances, and seizures, is well-known in many epileptic syndromes [ 67 , 68 , 69 ]. Few studies indicated the increased risk of sleep disturbances in patients with TSC [ 70 , 71 ]. However, none of the analyzed articles discussed the influence of sleep on DRE in individuals with TSC.…”
Section: Discussionmentioning
confidence: 99%
“…However, they are reported to be high in the limited studies on neurocutaneous syndromes, including NF1 and tuberous sclerosis complex. 2,3 Sleep is considered a vital brain state for optimizing memory consolidation, integration into long-term memory, and learning. 4 Impairment in sleep in children results in reduced neurocognitive functioning, leading to poor scholastic performance, behavioral and emotional problems.…”
Section: Introductionmentioning
confidence: 99%
“…6 In specific neurocutaneous syndromes, the prevalence of epilepsy and neurodevelopmental disorders are at higher rates than in the general pediatric population. 2,3 Seizures can cause disruption to the sleep architecture and alteration in rapid eye movement (REM) sleep. 7 Seizures result in sleep fragmentation, and the severity of seizures correlates with sleep disturbances.…”
Section: Introductionmentioning
confidence: 99%